Evaluation of changes in the expression of Wnt/β-catenin target genes in mouse reproductive tissues during estrous cycle: An experimental study - Saeed Zavareh; Zahra Gholizadeh; Taghi Lashkarbolouki (Shahid Sadoughi University of Medical Sciences, 2018)
Background: The Wingless-type (Wnt)/β-catenin signaling pathway controls cell homeostasis. Reproductive tissues are dynamic in response to steroidal hormone changes. Steroidal hormones are known to control the Wnt/β-catenin pathway, but their role in reproductive tissues remains unknown. Objective: The present study aims to investigate the expression patterns of Wnt/β-catenin target genes in mouse reproductive tissues during the normal estrous cycle. Materials and Methods: In this experimental study, 16 adult NMRI mice were grouped as proestrus, estrus, metestrus, and diestrus according to vaginal smear and histological evaluation of uterine and ovarian tissues. Uterine horns and ovarian tissues were collected. Reverse transcription quantitative polymerase chain reaction was performed to evaluate the expression of Wnt/β-catenin target genes (Myc2, Ppard, Id2, Birc5, and Ascl2) at different stages of the estrous cycle. Results: The expression levels of Id2, Ascl2, and Pprd in uterine tissue were significantly higher at the proestrus phase than at the other stages. Meanwhile, Birc5 expression in uterine tissue was significantly higher at the metestrus stage than at the other stages. Furthermore, Myc2 expression was significantly higher at the diestrus stage than at the estrus and metestrus stages. In the ovarian tissue, the highest expression of Id2, Ascl2, and Birc5 was detected at the proestrus stage, whereas the highest expression of Myc2 and Ppard was observed at the estrus stage. Conclusion: This study showed that Wnt/β-catenin target genes profiles are different among estrous cycle. It seems that different hormonal profiles during estrous cycles play a key role in the expression pattern of Wnt/β-catenin target genes in ovarian and uterine tissue.